PENGUATAN WIRAUSAHA TANI DALAM PENINGKATAN STATUS SOSIAL EKONOMI MELALUI PERAN PENTA HELIX PADA KELOMPOK TANI KOPI HUTAN DI DESA PANDUMAN - Mawardi, Ahmad Ahsin Kusuma; Farida, Lilik; Endhiarto, Tatok; Sundari, Sri; Indraningrat, Ketut (Jurnal Pengabdian Masyarakat Applied, 2024)
The Panduman Village Forest Coffee Farmers Group has great potential to develop but faces various problems in terms of production, human resources, institutions, marketing, and finance. This community service aims to 1) Increase the productivity of coffee production gardens through the socialization of Good Agricultural Practices (GAP) and Good Manufacturing Practice (GMP), 2) Increase knowledge of coffee farming entrepreneurs through nature schools, 3) Strengthen the institutionalization of coffee farming groups through mentoring for farming entrepreneurs, licensing and strengthening Bumdes, 3) Build a marketing network for farming entrepreneur partnerships, and 4) Build trust in funding sources through strengthening trust in banks and exporters. The methods used are lectures, discussions, demonstrations of methods, demonstrations of results, and evaluations. The results achieved from this community service activity are (1). Increased awareness of the care, maintenance, and harvesting processes (2). Strengthening farming entrepreneurs by processing coffee production gardens according to GAP SOPs and post-harvest processes through GMP SOP stages. (3). Some coffee farmers have proof of land ownership and Perhutani land cultivation letters, strengthening the entrepreneurial spirit of farmers, increasing the number of legal farmer entrepreneurs and strengthening the bargaining value of Bumdes as a business network partner for coffee farmer entrepreneurs. (4). Formal partnerships have been established, (5) There are partnerships between farmer groups, Bumdes, banks and exporters mediated by coffee farmer associations, (6) there is a realization of the disbursement of working capital funds from banks to coffee farmer groups and documented coffee farmers.